Numerical and experimental integration in analysis of a superplastic forming - Carunchio, A. F.; Batalha, M. H.F.; Pereira, D. A.; Resende, H. B.; Batalha, A. E.F. [UNESP]; Toloczko, F. R.; Santos, M. W.B.; Batalha, G. F. (Wiley, 2017)
Superplastic forming (SPF) is a technique that takes advantage of metallic alloys with fine grain size presenting very high ductility and large deformations before rupture under certain conditions. There is a growing interest in this manufacturing process in different areas, such as: aeronautical, automotive and medical, due to the possibility of fabricating complex geometry, lightweight, and strong thin shell parts. The researchers employed an industrial size superplastic hot press and, aiming to start investigations in the field of superplastic forming, finite element simulation and material analysis. This paper presents one of a first works in this field: developing a numerical model and forming a titanium alloy dome. A finite element model was developed to obtain the pressure curve, used as input in the superplastic forming machine control and for thickness prediction. Results and comparisons between the formed part and numerical calculations are presented, as well as the main difficulties the institutions faced in this new research field.
Keywords: bulge test; finite element; lightweight structures; shell manufacturing; Superplastic forming; titanium alloys